2022
DOI: 10.1590/1806-9282.20220248
|View full text |Cite
|
Sign up to set email alerts
|

Seroepidemiologic survey of the household contacts of leprosy patients

Abstract: OBJECTIVE: Leprosy is a disabling infectious disease caused by Mycobacterium leprae. This study aimed to investigate the prevalence of leprosy among household contacts of leprosy patients. METHODS: This study is a serological survey in household contacts of leprosy patients who had been treated or were undergoing treatment in the city of Presidente Prudente, São Paulo, Brazil, from 2006-2016, using clinical examination and screening for anti-Phenolic glycolipid-I antibodies with Mycobacterium leprae-flow serol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
2
0
1
Order By: Relevance
“…Besides these clinical forms and the operational classification of WHO, a major challenge in this chronic disease is the definition of subclinical infection or latent leprosy. Even in the absence of symptoms, M. leprae is replicating and invading the host tissues ( 5 ), and biomarkers for the infection as anti-phenolic glycolipid-I (PGL-I) IgM antibodies have been recommended to detect a risk of infection in asymptomatic patients, especially household contacts. Some studies have also suggested a relation between infection in these patients and other biomarkers such as IL-6 and nutritional status ( 6 ), serum levels of IgA antibodies against NDO-HSA ( 7 ), CCL2 chemokine associated with IFN-γ ( 8 ), and IgM profile against NDO-HSA, LID-1, and NDOLID antigens, and monocytes and CD4+ lymphocyte frequency ( 9 ), beyond arginase activity ( 10 ) as a protective marker against this infection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides these clinical forms and the operational classification of WHO, a major challenge in this chronic disease is the definition of subclinical infection or latent leprosy. Even in the absence of symptoms, M. leprae is replicating and invading the host tissues ( 5 ), and biomarkers for the infection as anti-phenolic glycolipid-I (PGL-I) IgM antibodies have been recommended to detect a risk of infection in asymptomatic patients, especially household contacts. Some studies have also suggested a relation between infection in these patients and other biomarkers such as IL-6 and nutritional status ( 6 ), serum levels of IgA antibodies against NDO-HSA ( 7 ), CCL2 chemokine associated with IFN-γ ( 8 ), and IgM profile against NDO-HSA, LID-1, and NDOLID antigens, and monocytes and CD4+ lymphocyte frequency ( 9 ), beyond arginase activity ( 10 ) as a protective marker against this infection.…”
Section: Introductionmentioning
confidence: 99%
“…Leprosy household contacts present a risk for the development of the disease (11) and could maintain the spread of the M. leprae even if the index case is treated since some studies have shown positive PCR for M. leprae DNA in samples as nasal swabs, nasal turbinate biopsies, and/or peripheral blood in asymptomatic cases (12)(13)(14)(15). Considering that positive results for anti-PGL-I IgM in these household contacts are associated with a higher risk of becoming ill, the evaluation and serology anti-PGL-I IgM of these individuals are recommended (5).…”
Section: Introductionmentioning
confidence: 99%
“…Mycobacterium lepromatosis (caractérisée par une longue incubation), d'évolution chronique et invalidante, qui affecte la peau et le système nerveux périphérique(1)(2)(3). La prise en charge est basée sur l'adhésion des populations concernées aux mesures de lutte, la détection des cas de lèpre et la chimiothérapie.…”
unclassified